Prevalence of integrality and associated factors in child health in municipalities of the 4th health region of Rio Grande do Sul - Carvalho, Jordana Lopes; Menegazzo, Gabriele Rissotto; Colomé, Juliana Silveira; Gomes, Bruna Cristiane Furtado; Streck, Mônica Tábata Heringer; Giordani, Jessye Melgarejo do Amaral; Weiller, Teresinha Heck (Journal of Health Care, 2021)
Aim: Investigate the prevalence of integrality attribute and associated factors in child health of the municipalities of the 4th Regional Health Coordination, Brazil. Materials and population consisted of family members/caregivers of children who access Primary Care services. For data collection, a characterization questionnaire and the Brazil Health Assessment Instrument for Primary Health in child version were used. Data analysis was performed using the Stata 14.0 program. Results: Of the total 1000 respondents, the prevalence of integrality was 45% (Confidence Interval: 41.9-48.1) in the assessed scenario. Children aged 12 to 18 years showed a 30% lower prevalence of the integrality attribute when compared to those up to 5 years of age. Conclusion: The caregivers of older children seek health services in Primary Health Care in a less integral way. The prevention of diseases and illnesses in children requires a set of measures to be taken, which must articulate the care to fewer limitations and more opportunities for children and their families to access health services in an integral manner, especially in the case of older children. It is expected that this study will contribute to the construction of new foundations and practices in health with relation to child’ health integrality.